Screen design with dynamic symmetry: A discovery - Ngo,, DCL; Ch'ng, , E (2005)
Hambidge's study of Greek art convinced him that the secret of the beauty of Greek design was in the conscious utilization of dynamic symmetry - the law of natural design based upon the symmetry of growth in man and in plants. While our study of dynamic symmetry that underlies 150 real screens shows an unmistakable use of plan schemes of the proportioning system in 61% of them, few adhere absolutely to it. Nevertheless, the evidence leads to the conclusion that layout was probably approximated by designers of great native ability whose sense of form is highly developed. (C) 2004 Elsevier Ltd. All rights reserved.